2021
DOI: 10.1101/2021.06.20.449155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An IRF4-MYC-mTORC1 integrated pathway controls cell growth and the proliferative capacity of activated B cells during B cell differentiationin vivo

Abstract: Cell division is an essential component of B cell differentiation to antibody-secreting plasma cells, with critical reprogramming occurring during the initial stages of B cell activation. However, a complete understanding of the factors that coordinate early reprogramming events in vivo remain to be determined. In this study, we examined the initial reprogramming by IRF4 in activated B cells using an adoptive transfer system and mice with a B cell-specific deletion of IRF4. IRF4-deficient B cells responding to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 93 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…IRF4 is a transcription factor lowly expressed in naïve cells, absent in GC B cells and upregulated in plasma cells (Willis et al, 2014). In particular, IRF4 has been shown to be important for regulating the proliferative capacity of B cells during activation and is required for early GC B cells formation in a B cell-intrinsic manner (Patterson et al, 2021;Willis et al, 2014). Thus, the lower expression of IRF4 by B cells from older donors may result in early proliferative defects, as previously reported (Blaeser et al, 2008) and contribute to the reduced early GC response, as we observed in our mouse The SW HEL adoptive transfer system allowed us to compare the function of B cells from young or aged donor mouse in responding to vaccination in vivo in a young environment.…”
Section: Discussionmentioning
confidence: 99%
“…IRF4 is a transcription factor lowly expressed in naïve cells, absent in GC B cells and upregulated in plasma cells (Willis et al, 2014). In particular, IRF4 has been shown to be important for regulating the proliferative capacity of B cells during activation and is required for early GC B cells formation in a B cell-intrinsic manner (Patterson et al, 2021;Willis et al, 2014). Thus, the lower expression of IRF4 by B cells from older donors may result in early proliferative defects, as previously reported (Blaeser et al, 2008) and contribute to the reduced early GC response, as we observed in our mouse The SW HEL adoptive transfer system allowed us to compare the function of B cells from young or aged donor mouse in responding to vaccination in vivo in a young environment.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing and assay for transposase-accessible chromatin with sequencing libraries RNA sequencing (RNA-seq) libraries were prepared from 1 × 10 5 CD4 1 CD44 lo RFP À population AD cells from the spleen and lymph nodes of Nur77-GFP Foxp3-IRES-RFP mice. Cells were sorted directly into RLT lysis buffer (Qiagen) with 1% 2-ME, sequenced, quality checked, and mapped to the mm10 genome as previously described (18). Genes expressed at 3 reads per million in all samples of one group were considered expressed.…”
Section: T Cell Stimulationmentioning
confidence: 99%
“…Genes expressed at 3 reads per million in all samples of one group were considered expressed. Assay for transposase-accessible chromatin with sequencing (ATAC-seq) libraries were prepared from 2 × 10 4 CD4 1 CD44 lo RFP À population AD cells from the spleen and lymph nodes of Nur77-GFP Foxp3-IRES-RFP mice, sequenced, and mapped to the mm10 genome as previously described (18).…”
Section: T Cell Stimulationmentioning
confidence: 99%
“…Although it is expressed in normal plasma cells, its transcription level steadily increases throughout MM progression 27,34,37,38 . Several studies in B cell malignancies, including MM, describe the binding of IRF4 to the MYC promoter and the creation of an autoregulatory feedback loop deregulating these two genes [39][40][41] . However, this is the first description of how binding of cMAF and IRF4 to a small non-coding regulatory region, changed the chromatin conformation and led to MYC activation in nontranslocated cell lines.…”
Section: Discussionmentioning
confidence: 99%